ANALISIS LINGUISTIK TERHADAP ISI SHORT MESSAGE SERVICE (SMS) YANG BERAKIBAT PELANGGARAN HUKUM - Hartini, Lilis (Jurnal Wawasan Yuridika, 2012)
Short Message Service (SMS)is a kind of written text as a means of making a long distant communication by using a mobile phone. Communication through Short Message Service frequently causes miscommunication among senders and receivers as there is no face to face communication. This failure of communication can cause various individual and social problems. The problems appear because the receiver is not happy or being threatened by the texts sent through Short Message Service. This failure of communication also causes violation against the law. The theory used in this research is functional grammar analysis; that is to say a way to make a research on texts contained in Short Message Service (SMS). This linguisticanalytic approach is aimed at examining rationality which is related to ideas of message senders, and also examining how it is consistent with other ideas. By using grammar and logic, the researcher studies this concept by analyzing from a certain point of view.This linguisticanalytic approach examines logically concepts according to the needs of the texts which have been approached. The result of the research shows that communication for people from different social and culture backgrounds can cause misunderstanding, so it can have an impact on legal action. When we make verbal and written communication with the strangers, we are supposed to understand attentively both explicit and implicit meanings of the texts. It should be consulted with the experts or linguists in order to avoid legal action.Keywords: short message service; violation against the law